Combination of denosumab and immune checkpoint inhibition: experience in 29 patients with metastatic melanoma and bone metastases - Angela, Yenny; Haferkamp, Sebastian; Weishaupt, Carsten; Ugurel, Selma; Becker, Jürgen C.; Oberndörfer, Florian; Alar, Vesna; Satzger, Imke; Gutzmer, Ralf (Cancer Immunology, Immunotherapy, 2019)
Background PD-1 inhibition (PD-1i) is the standard of care in melanoma and other malignancies. In patients with bone metastases of solid tumors, the monoclonal antibody denosumab directed against RANKL is approved for the prevention of skeletal-related events. However, RANKL is not only relevant in osteoclastogenesis, but also has immunological effects. Hence, we aimed at investigating, whether the combination of PD-1i and denosumab produces synergistic effects in metastatic melanoma treatment. Methods We retrospectively collected and analyzed clinical data of metastatic melanoma patients with bone metastases, who received PD-1i and denosumab therapy. Results 29 patients were identified with a median age of 60.7 years: 20 were male and 9 were female. 20 patients (69%) were in stage IV M1c and 9 (31%) in stage IV M1d; 52% had an increased serum LDH. 24 patients (83%) received PD-1i as first-line therapy and five patients (17%) as second- or third-line therapy. 13 patients received the triple combination nivolumab, ipilimumab and denosumab (N + I+D), 16 patients received PD-1i and denosumab (PD-1i + D). Within a median follow-up time of 19.8 months, 17 patients progressed with a median time to progression of 6 months. The objective response rate was 54% in the N + I + D group and 50% in the PD-1i + D group. Recalcification of bone metastases was radiologically observed in 18 (62%) patients. No unexpected treatment-related adverse events emerged. Conclusions The combination therapy of metastatic melanoma with PD-1i and denosumab was feasible without unexpected safety issues and showed a promising efficacy signal. Further investigation in prospective studies is needed.